Examination of the Depression Prevalence in a Turkish Sample - Beyazsacli, Mehmet (2020)
The aim of this study is to examine the effect size of depression in a Turkish sample with respect to gender and developmental periods. The studies of dissertation and articles completed during the period of 2004-2018 and covering Turkish sample have been examined through the method of Meta Analysis. The studies carried out, with the help of the depression measuring instruments, on a Turkish sample that has not taken any psychiatric diagnosis until that time, have been scanned through, by the use of the data bases such as; Google Academic, EBSCOhost and Web of Science. The criterion based sampling, which is one of the methods of sample selection, has been utilized. In the Meta Analysis; the effect value has been calculated through the use of the Cone Chart and Rank Relevancy Test of Begg and Mazumdar, Forest Chart analysis and Hedges’s g. The random effects model has been utilized in the analysis. The general effect size of the depression with respect to gender has been found to be at low level and on women at relatively higher level. The effect size; for childhood and adolescence periods, which are considered to be the developmental periods, has been found out to be at low level, on young adults and adults at insignificant level, on elders at medium level and on women at relatively higher level. The results have been discussed, within the scope of literature, from the point of view of the effects onwoman depression and elderliness.